Sleep Quality and Its Correlates Among Adolescents-Cross Sectional Study - Mohanambal, M.; Arunagirinathan, N.; Dhanaraj, FabiolaM.; Kalavathy, P. (Journal of Neonatal Surgery, 2025)
Sleep quality has a long-term impact on health leading to depression among adolescent students. We conducted a cross-sectional study to assess the prevalenceofsleepqualityanditsassociatedfactorsamongadolescentsofhigher secondary school. 514 adolescents from different schools were selected by the probability proportionate to size (PPS) method. The Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep quality among adolescents. Frequency distribution and percentage were identified as descriptive analysis whereas chi-square test was done. Variables that were found statistically significant (P < 0:05) were further analyzed using the logistic regression model. Theprevalenceofsleepqualityinthisstudywas39.1%. In an analysis, religions, place of residence, satisfaction with academic performance, relationship with friends or classmates, more use of internet per day, and use of internet before falling asleep were found to be statistically significant with sleep quality. The overall prevalence of sleep quality among school going adolescent students was 39.1 percent which was comparatively high